DETERMINANTS OF ACTUAL ELECTRONIC MEDICAL RECORD USE: A SYSTEMATIC REVIEW - Eka Setiawan; Tantri Yanuar Rahmat Syah; Edi Hamdi; Sandra Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This systematic literature review (SLR) aims to identify the key factors influencing the actual use of Electronic Medical Records in hospitals. Applying the PRISMA method, 184 articles were screened, with eight studies meeting strict inclusion criteria (2020–2025). The findings reveal that usage is shaped by the interplay of four key dimensions: technical, psychological, organizational, and social. Technically, system interoperability and data reliability are essential. Psychologically, user trust, satisfaction, and privacy perception drive sustained usage. Organizational support, including training and policies, enhances adoption, while social aspects such as digital literacy and access inequality influence successful implementation. This review highlights the need for a multidimensional and context-sensitive approach to ensure the effective integration of Electronic Medical Record systems in healthcare settings.